Gorlin Goltz Syndrome: A Case Report and Discussion on Diagnosis and surgical management - Mukul, Sailesh K; Kumar, Amit; Mokhtar, Ejaz Ahmad; Pandey, Shweta (Journal of Orofacial Research, 2017)
Gorlin Goltz syndrome (GGS) is a rare syndrome caused due to inheritance of autosomal dominant gene with the exception of sporadic mutation cases. The tumor suppressor gene known as Patched (PTCH) present in the 9q chromosome have been identified as the cause of GGS. Gorlin Goltz presents with a wide range of developmental anomalies and predisposition to neoplasm. It is of significance to rule out GGS in patients with multiple odontogenic keratocysts (OKT/OKC). To date, very few cases of GGS has been reported in India. We hereby present a case of multiple keratocysts in the mandible and maxilla, which on further evaluation revealed, various skeletal, facial and cutaneous anomalies leading to diagnosis of the Gorlin Goltz syndrome. This case report discusses clinical and radiological presentation of GGS and management of its different clinically presenting manifestations with special emphasis on OKT.